ANALYSIS OF STUDENTS' MATHEMATICAL REPRESENTATION ABILITY IN SOLVING DIVERGEN MATHEMATICS PROBLEMS IN VIEW OF GENDER DIFFERENCES - Rani Putri Angsi Sormin; Mesak Ratuanik (Jurnal Eduscience, 2023)
Abstract